Flexible Transparent Electrochemical Energy Conversion and Storage: From Electrode Structures to Integrated Applications. Issue 1 (12th June 2022) - Zhao, Yanli; Liu, Huaizhi; Yan, Yu; Chen, Tianwei; Yu, Huihuang; Ejeta, Lucky Ogheneakpobo; Zhang, Guanhua; Duan, Huigao
Abstract : The rapid progress of flexible electronics tremendously stimulates the urgent demands for the matching power supply systems. Flexible transparent electrochemical energy conversion and storage devices (FT–EECSDs), with endurable mechanical flexibility, outstanding optical transmittance, excellent electrochemical performance, and additional intelligent functions, are considered as preferable energy supplies for future self‐powered flexible electronic systems. A comprehensive review of the reasonable design of flexible transparent electrode and recent progress on the FT–EECSDs is presented herein. The manufacturing techniques of generally classified three types of flexible transparent electrodes are systematically summarized. Emphasis is given to the recent developments in the transparent solid‐state electrolyte, flexible transparent energy conversion, and storage devices. The standard evaluation methods and reasonable evaluation parameters to evaluate the flexibility and transparency of FT–EECSDs are highlighted. Additionally, the typical integrated applications of FT–EECSDs are also described. Finally, the current challenges and a future perspective on the research and development direction are further outlined. Abstract : This review shows the multi‐level integrated application of flexibility and transparence from electrodes, electrolytes, and devices to self‐powered systems and highlights the reasonable evaluation and testing methods for flexibility and transparence.